Preclinical Immune Response and Safety Evaluation of the Protein Subunit Vaccine Nanocovax for COVID-19 - Tran, Thi Nhu Mai; May, Bruce Pearson; Ung, Trong Thuan; Nguyen, Mai Khoi; Nguyen, Thi Thuy Trang; Dinh, Van Long; Doan, Chinh Chung; Tran, The Vinh; Khong, Hiep; Nguyen, Thi Thanh Truc; Hua, Hoang Quoc Huy; Nguyen, Viet Anh; et al. (Frontiers in Immunology, 2021)
The Coronavirus disease-2019 (COVID-19) pandemic caused by the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2), has become a dire global health concern. The development of vaccines with high immunogenicity and safety is crucial for control of the global COVID-19 pandemic and prevention of further illness and fatalities. Here, we report development of SARS-CoV-2 vaccine candidate, Nanocovax, based on recombinant protein production of the extracellular (soluble) portion of the S protein of SARS-CoV-2. The results showed that Nanocovax induced high levels of S protein-specific IgG, as well neutralizing antibody in three animal models including Balb/C mice, syrian hamsters, and non-human primate (Macaca leonina). In addition, the viral challenge study using the hamster model showed that Nanocovax protected the upper respiratory tract from SARS-CoV-2 infection. No adverse effects were induced by Nanocovax in mice (Mus musculus val. Albino), and Rats (Rattus norvegicus). These pre-clinical results indicated that Nanocovax is safe and effective.